2015
DOI: 10.1111/ipd.12213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a third‐generation LED LCU on microhardness of tooth‐colored restorative materials

Abstract: Based on the results of this study, it can be concluded that the high-power mode of the VALO LCU can be recommended for clinical applications especially in pediatric patients, as it can shorten the time required to adequately polymerize resin-based tooth-colored restorative materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
2
27
0
6
Order By: Relevance
“…However, in Cefley’s and Bayindir’s studies, top surface hardness in RMGI discs was higher than the bottom because they had cured only the top surfaces of their samples (27,28). However, some previous studies showed no significant differences in VHN of top and bottom surfaces of RMGI (29,30). The differences in VHN between top and bottom surfaces in this study might be attributed to more acid-base reactions because of the bulk of the samples at the bottom and probably to packing force on bottom surfaces.…”
Section: Discussionmentioning
confidence: 81%
“…However, in Cefley’s and Bayindir’s studies, top surface hardness in RMGI discs was higher than the bottom because they had cured only the top surfaces of their samples (27,28). However, some previous studies showed no significant differences in VHN of top and bottom surfaces of RMGI (29,30). The differences in VHN between top and bottom surfaces in this study might be attributed to more acid-base reactions because of the bulk of the samples at the bottom and probably to packing force on bottom surfaces.…”
Section: Discussionmentioning
confidence: 81%
“…However, the results of surface microhardness test obtained from materials except ACTIVA BioACTIVE restorative material were parallel with similar studies. 15,25,26 Based on these findings, RMGICs can be an alternative compomer or composite resin materials for permanent or especially primary dental restorations. In particular, ACTIVA BioACTIVE restorative, which contains a proprietary and flexible resin matrix with energy absorbing elastomeric components (a mixture of modified polyacrylic acid and polybutadiene modified diuretene dimethacrylate with a diurea-on and methacrylate) as stated by the manufacturer, can be used in high stress areas where glass ionomer cements are contraindicated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies had highlighted that the Valo LCU in high-power mode (1400 mW/cm 2 for 12 s) and in standard mode and the Elipar LCU produced similar microhardness values, on the surfaces of materials. However using the Valo LCU in extra mode (3200 mW/cm 2 for 6 s) resulted in the lowest microhardness values on the top and bottom surfaces of the tested materials [8]. Leprince et al stated that irradiation time was not the most important factor in adhesive polymerization, however it is important to achieve polymerization at greater depths [31].…”
Section: Discussionmentioning
confidence: 95%
“…In case of insufficient polymerization of resins, deterioration of the mechanical properties of cured materials, such as the increase of water sorption and a decrease in the hardness, may occur [7]. Poor polymerization of resin-based materials also adversely affects bond strength [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation